Expression profiles of miR-101-3p and miR-431-5p as potential diagnostic biomarkers for rheumatoid arthritis - Mohamed M. Sadaty; Salma M. Mekhemer; Shaimaa Abdel-Ghany; Amira R. El-Ansary; Rana Mohamed; Nashaat N. Kamal; Hussein Sabit (Scientific Reports)
Abstract Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by persistent inflammation of the synovial joints, leading to cartilage and bone destruction. This study aimed to evaluate the diagnostic utility of specific microRNAs (miRNAs) as potential biomarkers for RA. The study was conducted on 60 patients with RA disease along with 20 control participants. Comprehensive analysis of patient data, encompassing serological, hematological, and biochemical markers, revealed significantly elevated levels of miR-99b-5p, miR-101-3p, and miR-431-5p in RA patients compared to healthy controls. Among these, miR-101-3p demonstrated the highest diagnostic accuracy, with an area under the curve (AUC) of 0.873. These findings contribute to a deeper understanding of RA pathogenesis and suggest that miR-101-3p may serve as a valuable biomarker for early disease detection and potentially improved patient management. Further research is warranted to elucidate the precise mechanisms underlying miRNA involvement in RA and to explore their potential as therapeutic targets.